A case study on unit trust organisation with emphasis on Sekim Amanah Saham Nasional / Nihlah Abdullah - Abdullah, Nihlah (1985)
The objective of writting this modest case study is to get the writer acquinted with the operation of a Unit Trust organisation with emphasis on Sekim Amanah Saham Nasional.Futhermore unit trust's operation and its consept is an area which is not covered during my academic duration.These made the research for this case study very interesting and cahllenging